THE EFFECT OF USE OLIVE OIL ON BABY'S DIAPER - Dhiyan Nany Wigati; Ester Yohana Sitorus (The Shine Cahaya Dunia Kebidanan, 2021)
Background: One of the things that is important to do for babies is skin care, because the characteristics of baby's skin are very different from adult skin. Based on the anatomy and physiology of the skin, the skin in babies is relatively thin, smooth, the pH of the skin is acidic, and the inner layer has higher moisture, which can make the baby's skin prone to allergies and irritation. This irritation can result from prolonged exposure to diapers or diapers that are full of urine and feces.Methods: Test bivariate analysis in this study using the Wilcoxon analysis. The place for taking the research was public health center Brati. Sampling with non-probability sampling technique type purposive sampling. Samples were taken as many as 30 babies aged 0-12 months. The main instrument used in this study is the assessment format.Results: This study, which was conducted on 30 samples, showed that 46.7% of infants were at the age of 4-6 months; 70% of babies have diaper rash with reddish skin; after being given olive oil 46.7% of the babies had no diaper rash. The Wilcoxon test results obtained a significance value of 0.000 (p value <0.05), so there is an effect of the use of olive oil on diaper rash.Conlusion: There is an effect of using olive oil on diaper rash. Keywords: Olive Oil, Diaper Rash